Correlation Between Japanese EFL Learners’ Attitudes Toward L1 Dialects and Japanese English - Saito, Arifumi (International Journal of Linguistics, 2023)
This study explores how Japanese EFL learners’ mindset toward their own regional dialect in Japanese (L1) influences their attitudes toward Japanese English, a recognized variety of English from the viewpoint of “English as an International Language” (EIL). We aim to examine whether Japanese learners’ attitudes toward the L1 dialects they speak can be a criterion to judge who can accept and practice Japanese English positively. Fourteen Japanese college students were divided into two groups–Western and Northeastern Japan–based on the widely held idea that the Western dialect is popular a variety in Japan while the Northeastern dialect is less popular. Students participated in a survey about their dialects, read two articles about English varieties, and wrote about their ideas on Japanese English. The results show that all the students from Western Japan (7) were favorable about their Japanese dialects, and five showed positive attitudes toward Japanese English. In the Northeastern Japan group, more than half of the students showed negative mindsets toward their own Japanese dialects. The overall tendency was that those who answered favorably about their dialects showed positive attitudes toward Japanese English while those who were negative about their L1 dialect also showed negative attitudes toward Japanese English. The results suggest that Japanese EFL learners’ attitudes toward their L1 regional dialect and Japanese English are correlated. The findings can be a benchmark to predict who would agree or disagree with the idea of EIL and help us decide what approaches to take to introduce the concept.